Preparation method of high-rate silicon-carbon negative electrode material
By forming a porous carbon cladding layer in the silicon carbon negative electrode material, the problem of low reversible capacity at high magnification in the prior art is solved, high specific capacity and cycle stability are achieved, and battery fast charging for electric vehicles and hybrid vehicles is met. need.
Patent Information
- Application Number
- CN202411692287.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing silicon-carbon anode materials exhibit low reversible capacity at high magnifications, which cannot meet the commercial needs of pure electric vehicles and hybrid vehicles in the field of battery fast charging.
By slowly dropping the silane coupling agent into the aqueous alcohol solution, adding acetic acid to adjust the pH, then adding resin powder to form molecular bonds, combining natural spherical graphite and nano-silicon powder, evaporating through water bath and high-energy ball milling, and finally high-temperature carbonization is carried out. A porous carbon cladding is formed to improve the lithium ion transport channel.
It achieves high specific capacity and good cycle stability, significantly improves the high-rate charging and discharging performance of silicon carbon negative electrode materials, and meets the needs of the fast charging field of battery.
Smart Images

Figure CN119181794A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a high-rate silicon-carbon negative electrode material. Background Art
[0002] With the continuous progress of the electric vehicle industry, the requirements for battery performance are increasing, especially the pursuit of higher battery capacity and faster charging rate. Graphite materials have high safety performance and stable electrode structure, and show long cycle life in batteries. However, they are limited by their low specific capacity and obvious voltage hysteresis, and are currently only suitable for energy storage applications with medium energy density. In contrast, silicon-based negative electrode materials are regarded as the ideal choice for the next generation of high energy density lithium-ion battery negative electrode materials due to their advantages such as high theoretical capacity, low working potential, abundant reserves and environmental friendliness. They have great development value and application prospects. However, silicon-based materials still have problems such as significant volume expansion during lithium storage and low reversible capacity during high-rate charge and discharge. The existing technology is to compound silicon and carbon, use graphite to improve the conductivity of the material and alleviate the volume expansion of silicon, improve structural stability, and enhance the life of silicon-carbon negative electrode batteries, but silicon-carbon negative electrode materials still show low reversible capacity at high rates.
[0003] Therefore, there is an urgent need to provide a method for preparing a high-rate silicon-carbon negative electrode material to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and defects of the prior art, provide a method for preparing a high-rate silicon-carbon negative electrode material, and prepare a silicon-carbon negative electrode material with high performance. The obtained silicon-carbon negative electrode material has a high specific capacity, good cycle stability and high-rate charge and discharge performance, which can meet the commercial needs of pure electric vehicles and hybrid vehicles in the field of battery fast charging.
[0005] The objective of the present invention is achieved through the following technical solutions: A method for preparing a high-rate silicon-carbon negative electrode material comprises the following steps: S1. Slowly drip the silane coupling agent into the alcohol aqueous solution, then add acetic acid to adjust the pH to 3.5-5.5, and stir rapidly for 30 minutes to obtain solution A; S2. Add a certain amount of resin powder to solution A to obtain solution B; S3, mixing natural spherical graphite, nano silicon powder and anhydrous ethanol evenly, placing in a 50°C water bath, stirring and evaporating, until silicon-carbon composite powder C is obtained; S4, slowly drop solution B into the silicon-carbon composite powder C, stir rapidly for 30 minutes, let stand for 30-60 minutes, then place in a water bath at 100-120°C, stir while evaporating, and wait until the solvent evaporates completely to obtain powder D; S5, placing powder D into a high-energy ball mill for ball milling; S6. Carbonize the ball-milled powder D at high temperature to obtain the final silicon-carbon negative electrode material.
[0006] As a preferred technical solution of the present invention, the silane coupling agent in S1 is one of vinyltrimethoxysilane, vinyltriethoxysilane, and isocyanatepropyltriethoxysilane, the mass percentage of the silane coupling agent is 0.5%~2%, preferably 0.5%~1%, and the mass percentage of the alcohol aqueous solution is 98%~99.5%, preferably 99%~99.5%.
[0007] As a preferred technical solution of the present invention, the solute of the alcohol aqueous solution in S1 is ethanol or isopropanol, and the solution concentration is 10% to 25%.
[0008] As a preferred technical solution of the present invention, the resin powder in S2 is one of epoxy resin, phenolic resin, polystyrene, polypropylene, and polytetrafluoroethylene, and the mass ratio of the resin powder to solution A is 1:20-50.
[0009] As a preferred technical solution of the present invention, the mass ratio of natural spherical graphite, nano silicon powder and anhydrous ethanol in S3 is 8-9:1-2:20-50.
[0010] As a preferred technical solution of the present invention, the mass ratio of the silicon-carbon composite powder C to the solution B in S4 is 1:2-5.
[0011] As a preferred technical solution of the present invention, the ball milling time in S5 is 5-12 hours and the rotation speed is 200-500 r / min.
[0012] As a preferred technical solution of the present invention, the high temperature carbonization in S6 is specifically: in an inert gas atmosphere, the temperature is increased to 800-900°C at a heating rate of 2-5°C / min, and carbonized for 60-120 minutes.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention allows a silane coupling agent to be slowly dripped into an alcohol aqueous solution, acetic acid is added to adjust the pH value to 3.5-5.5, so that the silane coupling agent can be quickly hydrolyzed, and then resin powder is added to react the CY functional group of the silane coupling agent with the resin powder to form a strong molecular bond. Natural spherical graphite and nano silicon powder are fully mixed in anhydrous ethanol to uniformly adsorb the nano silicon powder on the spherical graphite, and a silicon-carbon composite material is obtained after stirring and evaporating in a water bath. Solution B is then slowly dripped into the obtained silicon-carbon composite material to allow the Si-X functional group of the silane coupling agent to combine with silicon-carbon. Granulation and shaping are achieved through high-energy ball milling to improve the battery rate performance. Finally, the resin powder is carbonized at high temperature to form a uniform coating layer, the coating layer has a porous structure, can provide more lithium ion transmission channels, can achieve a higher reversible capacity at a high rate, and can meet the commercial needs of pure electric vehicles and hybrid electric vehicles in the field of battery fast charging. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a process flow chart of the present invention.
[0015] Figure 2 This is a test diagram of the electrochemical performance of Example 1 of the present invention.
[0016] Figure 3 This is a graph showing the electrochemical performance test of Example 2 of the present invention.
[0017] Figure 4 This is a test diagram of the electrochemical performance of Example 3 of the present invention. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0019] The specific implementation process of the present invention is as follows: like Figure 1 As shown, a method for preparing a high-rate silicon-carbon negative electrode material comprises the following steps: S1. Slowly drip the silane coupling agent into the alcohol aqueous solution, then add acetic acid to adjust the pH to 3.5-5.5, and stir rapidly for 30 minutes to obtain solution A; S2. Add a certain amount of resin powder to solution A to obtain solution B; S3, mixing natural spherical graphite, nano silicon powder and anhydrous ethanol evenly, placing in a 50°C water bath, stirring and evaporating, until silicon-carbon composite powder C is obtained; S4, slowly drop solution B into the silicon-carbon composite powder C, stir rapidly for 30 minutes, let stand for 30-60 minutes, then place in a water bath at 100-120°C, stir while evaporating, and wait until the solvent evaporates completely to obtain powder D; S5, placing powder D into a high-energy ball mill for ball milling; S6. Carbonize the ball-milled powder D at high temperature to obtain the final silicon-carbon negative electrode material.
[0020] Optionally, first, the silane coupling agent is slowly dripped into a pre-prepared alcohol-water solution, and the slow dripping can avoid excessive local concentration and ensure that the silane coupling agent can be evenly dispersed; then acetic acid is added to adjust the pH in the range of 3.5-5.5, and the solution is rapidly stirred for 30 minutes to obtain solution A. Acetic acid as a catalyst can accelerate hydrolysis, and the silane coupling agent has a more stable chemical shape when the pH is in the range of 3.5-5.5. Then, resin powder is added to solution A, and the mixture is stirred thoroughly to allow the CY functional group of the silane coupling agent to react with the resin powder to form a strong molecular bond, thereby obtaining solution B. Natural spherical graphite with good isotropy, nano silicon powder and anhydrous ethanol are mixed evenly, and the nano silicon powder is evenly adsorbed on the surface of the natural spherical graphite, and the mixture is placed in a 50°C water bath, stirred while evaporating, and the anhydrous ethanol is completely evaporated to obtain silicon-carbon composite powder C, i.e., silicon-carbon composite material. Solution B is slowly added dropwise to the silicon-carbon composite powder C, and the mixture is stirred rapidly for 30 minutes and then allowed to stand for 30 to 60 minutes to allow the amphiphilic group of the silane coupling agent to fully combine with the silicon-carbon and resin powders, and then placed in a 100 to 120°C water bath, stirred while evaporating, and the Si-X functional group of the silane coupling agent is combined with the silicon-carbon, and the solvent is completely evaporated to obtain powder D. Powder D is placed in a high-energy ball mill for ball milling at a speed of 200-500r / min and a ball milling time of 5-12h. Through high-energy ball milling, granulation shaping can be achieved to improve the battery rate performance. Finally, after high-temperature carbonization, the resin powder forms an amorphous porous carbon coating layer, which is evenly covered on the silicon-carbon negative electrode material to improve its structural stability and rate performance. All of the above mixing processes are completed in the liquid phase, so the mixing effect is good and the isotropy is high. At the same time, the coating layer formed by resin carbonization has a porous structure, which can provide more lithium ion transmission channels and achieve a higher reversible capacity at a high rate, which can meet the commercial needs of pure electric vehicles and hybrid vehicles in the field of battery fast charging.
[0021] The present invention will be further described below in conjunction with specific embodiments. Example 1
[0022] Vinyl trimethoxysilane was slowly dripped into a 10% isopropanol aqueous solution, the mass percentage of vinyl trimethoxysilane was 1%, and the mass percentage of isopropanol aqueous solution was 99%, and then acetic acid was added to adjust the pH of the solution to 3.9, and the solution was stirred rapidly for 30 minutes to obtain solution A. Polystyrene powder was added to solution A and mixed evenly to obtain solution B, and the mass ratio of the above polystyrene to solution A was 1:30. Natural spherical graphite, nano silicon powder, and anhydrous ethanol were mixed evenly in a mass ratio of 9:1:20, placed in a 50°C water bath, and evaporated while stirring until silicon-carbon composite powder C was obtained. Solution B was slowly dripped into silicon-carbon composite powder C, stirred rapidly for 30 minutes, and then allowed to stand for 30 minutes, and then placed in a 120°C water bath, stirred and evaporated, and the solvent was completely evaporated to obtain powder D, and the mass ratio of the above solution B to silicon-carbon composite powder C was 1:2. Powder D was placed in a high-energy ball mill for ball milling for 8 hours at a speed of 400 r / min. After the ball milling was completed, the powder was placed in a tube furnace, nitrogen was introduced for a period of time, and the temperature was raised to 900°C at a rate of 2°C / min and carbonized for 60 minutes to obtain the final silicon-carbon negative electrode material. Electrochemical performance tests were performed, such as Figure 2 As shown, at a current of 2A / g, the first efficiency is 83%, the first discharge specific capacity is 830mAh / g, and the capacity is still 226 mAh / g after 100 cycles of charge and discharge tests. Example 2
[0023] Vinyl triethoxysilane was slowly dripped into a 15% ethanol aqueous solution, the mass percentage of vinyl triethoxysilane was 0.5%, and the mass percentage of isopropanol aqueous solution was 99.5%, and then acetic acid was added to adjust the pH of the solution to 3.9, and stirred rapidly for 30 minutes to obtain solution A. Polypropylene powder was added to solution A and mixed evenly to obtain solution B, and the mass ratio of the above polypropylene to solution A was 1:20. Natural spherical graphite, nano silicon powder, and anhydrous ethanol were mixed evenly in a mass ratio of 8:2:40, placed in a 50°C water bath, and evaporated while stirring until silicon-carbon composite powder C was obtained. Solution B was slowly dripped into silicon-carbon composite powder C, stirred rapidly for 30 minutes, and then stood for 30 minutes, and then placed in a 100°C water bath, stirred and evaporated, and powder D was obtained when the solvent was completely evaporated. The mass ratio of the above solution B to silicon-carbon composite powder C was 1:3. Powder D was placed in a high-energy ball mill for ball milling for 12 hours at a speed of 400 r / min. After the ball milling was completed, powder D was placed in a tube furnace, nitrogen was introduced for a period of time, and the temperature was raised to 900°C at a rate of 5°C / min and carbonized for 120 minutes to obtain the final silicon-carbon negative electrode material. Electrochemical performance tests were performed, such as Figure 3As shown, at a current of 2A / g, the first efficiency is 78%, the first discharge specific capacity is 1233mAh / g, and the capacity is still 335 mAh / g after 100 cycles of charge and discharge tests. Example 3
[0024] Slowly drip isocyanate propyl triethoxysilane into a 25% ethanol aqueous solution, the mass percentage of isocyanate propyl triethoxysilane is 0.5%, and the mass percentage of isopropanol aqueous solution is 99.5%, then add acetic acid, adjust the pH of the solution to 4.5, and stir rapidly for 30 minutes to obtain solution A. Add polypropylene powder to solution A and mix evenly to obtain solution B, the mass ratio of the above polypropylene to solution A is 1:50. Natural spherical graphite, nano silicon powder, and anhydrous ethanol are mixed evenly in a mass ratio of 9:1:50, placed in a 50°C water bath, and evaporated while stirring until silicon-carbon composite powder C is obtained. Slowly drip solution B into silicon-carbon composite powder C, stir rapidly for 30 minutes, let stand for 30 minutes, and then place in a 100°C water bath, evaporate while stirring, and wait until the solvent evaporates completely to obtain powder D. The mass ratio of the above solution B to silicon-carbon composite powder C is 1:3. Powder D was placed in a high-energy ball mill for ball milling for 4 hours at a speed of 500 r / min. After the ball milling was completed, powder D was placed in a tube furnace, nitrogen was introduced for a period of time, and the temperature was raised to 800°C at a rate of 3°C / min and carbonized for 60 minutes to obtain the final silicon-carbon negative electrode material. Electrochemical performance tests were performed, such as Figure 4 As shown, at a current of 2A / g, the first efficiency is 80%, the first discharge specific capacity is 693mAh / g, and the capacity is still 291 mAh / g after 100 cycles of charge and discharge tests.
[0025] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a high-rate silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1. Slowly drip the silane coupling agent into the alcohol aqueous solution, then add acetic acid to adjust the pH to 3.5-5.5, and stir rapidly for 30 minutes to obtain solution A; S2. Add a certain amount of resin powder to solution A to obtain solution B; S3, mixing natural spherical graphite, nano silicon powder and anhydrous ethanol evenly, placing in a 50°C water bath, stirring and evaporating, until silicon-carbon composite powder C is obtained; S4, slowly drop solution B into the silicon-carbon composite powder C, stir rapidly for 30 minutes, let stand for 30-60 minutes, then place in a water bath at 100-120°C, stir while evaporating, and wait until the solvent evaporates completely to obtain powder D; S5, placing powder D into a high-energy ball mill for ball milling; S6. Carbonize the ball-milled powder D at high temperature to obtain the final silicon-carbon negative electrode material.
2. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The silane coupling agent in S1 is one of vinyl trimethoxy silane, vinyl triethoxy silane and isocyanate propyl triethoxy silane, the mass percentage of the silane coupling agent is 0.5% to 2%, and the mass percentage of the alcohol aqueous solution is 98% to 99.5%.
3. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The solute of the alcohol aqueous solution in S1 is ethanol or isopropanol, and the solution concentration is 10% to 25%.
4. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The resin powder in S2 is one of epoxy resin, phenolic resin, polystyrene, polypropylene and polytetrafluoroethylene, and the mass ratio of the resin powder to solution A is 1:20-50.
5. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of natural spherical graphite, nano silicon powder and anhydrous ethanol in S3 is 8-9:1-2:20-50.
6. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the silicon-carbon composite powder C to the solution B in the S4 is 1:2-5.
7. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The ball milling time in S5 is 5-12 hours, and the rotation speed is 200-500 r / min.
8. The method for preparing a high-rate silicon-carbon negative electrode material according to claim 1, characterized in that: The high temperature carbonization in S6 is specifically as follows: in an inert gas atmosphere, the temperature is raised to 800-900° C. at a heating rate of 2-5° C. / min, and the carbonization is performed for 60-120 minutes.
Citation Information
Patent Citations
High-capacity silicon-carbon composited anode material, preparation method and application thereof
CN102637872A
High-performance silicon monoxide / amorphous carbon / graphite composite negative electrode material and preparation method thereof
CN103258988A
Preparation method of lithium ion battery silicon-carbon composite cathode material
CN103515582A
Silicon-based composite negative electrode material for lithium ion battery
CN104241621A
Natural graphite-based silicon-carbon composite negative electrode material and preparation method and application thereof
CN113161521A
Cited By
High-stability spherical graphite and silicon negative electrode material combined with two-dimensional material and preparation method and application thereof
CN120440898A
